PH‐Responsive Fe(III)–Gallic Acid Nanoparticles for In Vivo Photoacoustic‐Imaging‐Guided Photothermal Therapy. Issue 7 (4th February 2016) - Zeng, Jianfeng; Cheng, Ming; Wang, Yong; Wen, Ling; Chen, Ling; Li, Zhen; Wu, Yongyou; Gao, Mingyuan; Chai, Zhifang
Abstract : pH‐responsive biocompatible Fe(III)–gallic acid nanoparticles with strong near‐infrared absorbance are very stable in mild acidic conditions, but easily decomposed in neutral conditions, which enables the nanoparticles to be stable in a tumor and easily metabolized in other organs, thus providing a safe nanoplatform for in vivo photoacoustic imaging/photothermal therapy theranostic applications.